Analisis Pengaruh Kemampuan Intelektual terhadap Hasil Belajar Mahasiswa dengan Penggunaan Media E-Learning sebagai Variabel Intervening : (Studi Kasus Mahasiswa Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Putra Indonesia “YPTK” Padang) - Yuli Angraini (Journal Of Business, Finance, and Economics (JBFE), 2024)
Intellectual ability is the ability of an individual to carry out mental activities and think clearly based on knowledge. By utilizing technological developments present in the world of education, one of which is the use of E-learning media, students can better understand the material provided with several benefits such as efficiency and effectiveness. This research method was carried out on students from the Faculty of Economics and Business, majoring in Management, Putra Indonesia University "YPTK" Padang. The sample used was 100 respondents using a purposive sampling technique. The data analysis used is primary and secondary data. The results of this research discussion show that: 1) Intellectual ability (X) has a positive and significant effect on student learning outcomes (Y). Based on the t-test results above, it can be seen that the unstandardized coefficients value is 0.277, and the significance value of the intellectual ability variable is 0.000 < 0.05; 2) The use of E-learning Media (Z) improves student learning outcomes (Y). Based on the t-test results above, it can be seen that the unstandardized coefficients value is 0.725 and the significance value of the intellectual ability variable is 0.000 < 0.05; 3) The intellectual ability test (X) is indirectly mediated by the use of e-learning media (Z) on student learning outcomes (Y) based on the results of path analysis showing that there is an indirect influence of the variable use of E-Learning media on student learning outcomes through intellectual ability with a total influence of 0.204 + (0.613 x 0.135) = 0.952.